CONSUMER ATTITUDES TOWARDS HYDROPONIC VEGETABLES IN NORTHERN THAILAND - เตชะมณีสถิตย์, ปรียานุช (RMUTT Global Business and Economics Review, 2017)
This paper explores the concept of consumer attitudes and relevant behaviour on hydroponic vegetable in Northern Thailand as we hope to promote efficiency modern agricultural methods. Three focus group sessions of 21 participants were created to explore the issues. These participants were asked questions and their views on the topic were discussed. An online survey was conducted. The system automatically deleted responses from participants who were outside northern Thailand. A total of 450 questionnaires (155 males, 285 females) were retained as they were completed by respondents in the northern Thailand region. The main question asked concerned participants’ understanding of hydroponic vegetables. The questionnaire also inquired into how growers and sellers can create product value. Giving information to potential customers about the product can help create a market or increase the market demand for the product. Survey results suggest that, Thai people have a positive attitude towards hydroponic vegetables as they view it as clean as no chemicals and insecticides are used in the production of such products. However, many people still do not know about hydroponic vegetables and fruit, therefore an information campaign could facilitate confidence in the product, and thereby create a greater market share for the product. Moreover, cleanliness, packaging, trust, distribution and promotions are also important factors, which can increase shopping experience for the customer.